A class of nonparametric mode estimators. Issue 6 (3rd June 2022) - Ruzankin, Pavel S.
Abstract: A class of nonparametric mode estimators is proposed. While the widely applied half sample mode estimators use the diameter of a set as the "measure of concentration", the proposed estimators use for it some types of "variance measures". In some cases, the new estimators perform better than half sample mode and half range mode estimators. Strong consistency is proved for an estimator from the class.